A large family of filled skutterudites stabilized by electron count - Luo, Huixia; Krizan, Jason W.; Muechler, Lukas; Haldolaarachchige, Neel; Klimczuk, Tomasz; Xie, Weiwei; Fuccillo, Michael K.; Felser, Claudia; Cava, Robert J. (Nature Communications, 2015)
The Zintl concept is important in solid-state chemistry to explain how some compounds that combine electropositive and main group elements can be stable at formulas that at their simplest level do not make any sense. The electronegative elements in such compounds form a polyatomic electron-accepting molecule inside the solid, a 'polyanion', that fills its available energy states with electrons from the electropositive elements to obey fundamental electron-counting rules. Here we use this concept to discover a large family of filled skutterudites based on the group 9 transition metals Co, Rh, and Ir, the alkali, alkaline-earth, and rare-earth elements, and Sb 4 polyanions. Forty-three new filled skutterudites are reported, with 63 compositional variations - results that can be extended to the synthesis of hundreds of additional new compounds. Many interesting electronic and magnetic properties can be expected in future studies of these new compounds.
CRIS-Team Scopus Importer:2023-03-20